User support as moderator for cloud computing user satisfaction. (10th May 2019) - Guimaraes, Tor; Paranjape, Ketan
Cloud computing (CC) promises to provide quicker, easier, and less expensive computing services supporting e-commerce. To ensure that CC is also able to maintain or enhance customer satisfaction, this study addresses the factors leading to higher user satisfaction with SaaS applications websites. The proposed model defines and empirically tests these relationships, including the moderating effect of user support. Data collected from 1, 257 users/customers using the order entry systems of 176 client organisations available through four SaaS providers were analysed. Results confirm the importance of the proposed success factors for user satisfaction with the CC vendor websites. Management of CC application risks, knowledge about the service provider, and effective data management respectively explained significant percentages of the variance in user satisfaction with the CC vendor website. The positive impact of user support is also confirmed. The results provide the basis for several insights and recommendations for managers and future research.